Prevalence of burnout and associated factors among health professionals working in public health facilities of Dire Dawa city administration, Eastern Ethiopia - Ahmed, Fila; Hawulte, Behailu; Yuya, Mohammed; Birhanu, Simon; Oljira, Lemessa (Frontiers in Public Health, 2022)
Background: Burnout is a common condition among health workers, characterized by emotional tiredness, depersonalization, and a sense of low personal accomplishment. Ethiopia has major health workforce management challenges, including shortages, poor motivation, retention, and performance, and research evidence is limited for health professionals’ burnout status, particularly in Eastern Ethiopia. Therefore, this study is aimed at determining the prevalence of burnout and associated factors among health professionals working at governmental health facilities in Eastern Ethiopia. Method: An institutional-based cross-sectional study was conducted among health professionals using structured self-administered validated questionnaires using the Maslach Burnout Inventory scale. Data were entered into Epi-Data version 3.1 and exported to SPSS version 22 for analysis. Multivariable logistic regression was used to determine the association between burnout and its predictors. Results: A total of 508 health professionals were approached, out of which 501 participated (a response rate of 98.4%). The magnitude of burnout was 54.1% with a 95% confidence interval of 49.9% to 58.0%. Working in a hospital [AOR= 3.55, 95%CI: 2.00, 6.33], age >/= 40 [AOR=3.98, 95%CI:1.60, 9.89] and 30-39 years [AOR= 1.90, 95%CI:1.08, 3.34], being female[AOR=2.41, 95%CI: 1.37, 4.25], being widowed [AOR=3.39, 95%CI: 1.13, 10.18], having intention of leaving work[AOR=2.28, 95%CI: 1.35, 3.87], using at least one substance [AOR=2.24, 95%CI: 1.36, 3.69], having a 6-11 years of experience [AOR=2.17, 95%CI: 1.15, 4.06], having no job supervision [AOR=4.65, 95%CI: 2.07, 10.43], monthly payment less than 10000 Ethiopian Birr [AOR=5.69, 95%CI: 2.30, 14.07] and between 10000 to 15000 Ethiopian Birr [AOR=2.74, 95%CI: 1.22, 6.15],working in Pediatric Unit[AOR=3.28, 95%CI: 1.24, 8.70], and profession type(Midwifery, Public health officer, Medical Laboratory professionals)were factors significantly associated with burnout. Conclusion: Burnout affected more than half of the health professionals working in governmental health facilities in Dire Dawa. Health facility type, age, sex, marital status, intention to leave work, substance use, work experience, job supervision, monthly payment, profession type, and working unit were significantly associated predictors of burnout. Keywords: